Cognitive impairment in bipolar disorder in comparison to mild cognitive impairment and dementia: a systematic review - Simjanoski,Mario (2022)
Abstract Objective To conduct a systematic review to describe cognitive abilities in bipolar disorder (BD) in comparison to cognitive abilities in mild cognitive impairment (MCI) and dementia. Methods A literature search was performed with no year or language restrictions. The search yielded 1,461 articles, with 1,261 remaining after removal of duplicates, five of which were suitable for the systematic review: two for the comparison between BD and MCI and three comparing BD and dementia. Results Analyses from our systematic review showed that euthymic individuals with BD present impairments in cognitive domains such as attention and executive functioning, motor skills, conceptual thinking, and visuo-spatial abilities that are equally severe as or more severe than the impairments observed in individuals with MCI. In contrast, studies comparing BD and dementia indicated that Alzheimer’s disease (AD) dementia and behavioral variant frontotemporal dementia (bvFTD) both showed greater cognitive deficits than BD during euthymia, whereas BD during a mood episode demonstrated higher cognitive impairments than bvFTD. Conclusion Findings from our systematic review suggest that cognitive impairments in euthymic BD fall into a range between the impairments seen in MCI and those seen in dementia. More studies are needed to analyze these comparisons, while also focusing on comparing different clinical stages of BD with MCI and dementia to analyze the progression of the clinical course and cognitive dysfunction in BD.PROSPERO registration ID: CRD42020150412